2020
DOI: 10.1007/s10765-019-2580-7
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing and Silicon Integration of Photoacoustic Gas Cells

Abstract: Downsizing and compatibility with MEMS silicon foundries is an attractive path towards a large diffusion of photoacoustic trace gas sensors. As the photoacoustic signal scales inversely with the chamber volume, a trend to miniaturization has been followed by several teams. We review in this article the approach initiated several years ago in our laboratory. Three generations of components, namely a 40 mm 3 3D-printed cell, a 3.7 mm 3 silicon cell, and a 2.3 mm 3 silicon cell with a builtin piezoresistive press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…While many efforts are aimed at improving sensitivity, the long-standing goal of miniaturization of these setups to make them portable is being pursued as well. In terms of miniaturization, 3-D printers and silicon technology have been used to build simpler and smaller setups with diminished performances but at much lower cost and requiring less infrastructure [88][89][90][91][92][93][94].…”
Section: Acoustic Resonator-enhanced Photoacoustic Spectroscopymentioning
confidence: 99%
“…While many efforts are aimed at improving sensitivity, the long-standing goal of miniaturization of these setups to make them portable is being pursued as well. In terms of miniaturization, 3-D printers and silicon technology have been used to build simpler and smaller setups with diminished performances but at much lower cost and requiring less infrastructure [88][89][90][91][92][93][94].…”
Section: Acoustic Resonator-enhanced Photoacoustic Spectroscopymentioning
confidence: 99%
“…Weigl utilized a 3D-printed aluminum cell in a photoacoustic trace gas sensor to optimize light coupling while minimizing background signal generation, achieved through a specially designed cell structure and the incorporation of a spirally formed gas channel for gas heating prior to detection . Additionally, metal cells showed promise for photoacoustic gas cells, demonstrating high integration and practicality with customized structure designs . Given that sensor cells come into direct contact with gases, it is crucial to consider the corrosion resistance of the 3D printing materials, particularly when detecting corrosive target gases.…”
Section: D-printed Gas Sensing Modulesmentioning
confidence: 99%
“…197 Additionally, metal cells showed promise for photoacoustic gas cells, demonstrating high integration and practicality with customized structure designs. 198 Given that sensor cells come into direct contact with gases, it is crucial to consider the corrosion resistance of the 3D printing materials, particularly when detecting corrosive target gases. In Bonilla-Manrique's work, the target gas was H 2 S, and a resonant gas cell was employed for a photoacoustic sensor.…”
Section: D-printed Functional Componentsmentioning
confidence: 99%
“…Lhermet et al reported a micro photoacoustic cell with integrated piezoresistive cantilever microphone [77] , [78] , [79] . This is the third-generation device of miniature photoacoustic components at CEA-LETI (a laboratory in French Atomic Energy and Alternative Energy Commission).…”
Section: Cepas Based On Different Displacement Detection Techniquesmentioning
confidence: 99%
“…
Fig. 9 The photoacoustic sensor of CEA-LETI [79] . (a)Structure of the silicon-integrated sensor (left) and photo of the manufactured chip (right).
…”
Section: Cepas Based On Different Displacement Detection Techniquesmentioning
confidence: 99%